Analisis Kesulitan Belajar Siswa Materi Perkalian Matriks di Kelas XI SMAK ST. Dominikus Tambolaka - Sistina Lende; Samuel Rex M. Making; Geterudis Kerans; Yulius K. Lede (Constructivism: Journal of Research in Education, 2024)
Mathematics is a fundamental discipline that plays an important role in developing logical and systematic thinking skills. However, many students experience difficulties in understanding mathematical concepts, particularly in matrix operations. These difficulties often affect students’ ability to solve mathematical problems correctly. Therefore, it is important to analyze students’ learning difficulties in order to identify the factors that hinder their understanding and problem-solving abilities. This study aims to analyze the learning difficulties experienced by eleventh-grade students in solving matrix multiplication problems at SMAK St. Dominikus Tambolaka. The research employed a mixed methods approach that combines quantitative and qualitative methods. The quantitative method was used to analyze students’ test results, while the qualitative method was used to describe students’ learning difficulties in terms of conceptual, procedural (skills), and principle aspects. The research subjects consisted of all students of class XI Religion at SMAK St. Dominikus Tambolaka. Data were collected through written tests, interviews, and documentation. The results of the study indicate that students experience three main types of learning difficulties in matrix multiplication. Conceptual difficulties occur when students are unable to identify known and asked information in a problem and do not fully understand the properties of matrix multiplication. Skill difficulties arise when students make errors in performing matrix operations due to lack of accuracy in calculations. Principle difficulties occur when students are unable to recall or apply the correct formula for matrix multiplication. These findings indicate that students’ understanding of matrix multiplication concepts is still relatively low. Therefore, teachers are encouraged to implement more varied learning strategies that emphasize conceptual understanding and provide more practice opportunities in solving matrix multiplication problems.